Evolusi Ekonomi Syariah Dalam Marketplace: Analisis Shopee - Cinta Rahmi; Lulu Fatimah Azzahra; Dinna Chaerun Nisa; Dendi Anugrah (CV. ITTC INDONESIA, 2024)
The way the sharia economy has developed in the marketplace—as demonstrated by the Shopee platform—indicates that it is always evolving and adapting to the demands of the digital market. This study examined Shopee's sharia economy and discovered a number of intriguing findings.In online marketplaces like Shopee, the sharia economy is growing significantly. Analysis indicates that Shopee's sharia economy is growing faster than the traditional economy. One of the industries influencing Shopee's sharia economy is sharia finance. The sharia economy is being driven by newcomers and small companies in the internet market. One of the things propelling the sharia economy in the digital market is the existence of platforms such as Shopee. One element affecting the sharia economy in the digital market is the COVID-19 epidemic. The growth of sharia economy at Shopee is influenced by government policies that support sharia economics. On Shopee, customers who require sharia goods or services turn into sharia economic drivers. At Shopee, technology that facilitates spending and transactions is what powers the sharia economy.According to this study, the Islamic economy is growing faster than the mainstream economy in online marketplaces like Shopee. The sharia economy in the digital market is fueled by a number of variables, including sharia financing, platforms, pandemics, startups and small enterprises, customers, and technology.